Pengaruh Kemampuan Disposisi Matematis terhadap Kemampuan Berpikir Kritis Matematis Siswa - Nurma Izzati; Nurul Habibah (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
The primary objective of this study is to examine the extent to which mathematical disposition influences mathematical critical thinking ability. This study employed a quantitative approach with an explanatory research design. The sample consisted of 37 students from class VII-D at SMP Negeri 7 Kota Cirebon, selected through the cluster random sampling method. Two primary instruments were utilized that is a mathematical critical thinking test comprising 8 questions and a mathematical disposition questionnaire with 35 items, which has met the validity criteria and can be used to assess students' mathematical dispositions. Data analysis involved normality testing, Pearson correlation calculations, and F and t tests within a simple linear regression framework. The results indicate that the data are normally distributed, the variances are homogeneous, and both variables show a significant relationship with a correlation coefficient of 0.78. The results of this study indicate that mathematical disposition as an affective factor affects students’ mathematical critical thinking skills. Consequently, this factor can be considered in mathematics learning, assist teachers in selecting appropriate teaching strategies, and provide new insights into the role of mathematical disposition in supporting students’ mathematical critical thinking.